2018
DOI: 10.1039/c8gc00557e
|View full text |Cite
|
Sign up to set email alerts
|

BINAP-copper supported by hydrotalcite as an efficient catalyst for the borrowing hydrogen reaction and dehydrogenation cyclization under water or solvent-free conditions

Abstract: A BINAP-Cu system supported by hydrotalcite has been developed and proved to be a highly efficient catalyst for the atom-efficient and green borrowing hydrogen reaction and dehydrogenative cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 111 publications
(38 citation statements)
references
References 68 publications
1
37
0
Order By: Relevance
“…1‐(4‐bromophenyl)‐3‐(4‐chlorophenyl)propan‐1‐one (3 be) Yield 294.5 mg 91 % (Catalyst Ru1 ), 300.9 mg 93 % (Catalyst Ru2 ); 1 H NMR (400 MHz, CDCl 3 ) δ 7.78 (d, J =8.6 Hz, 2H), 7.57 (d, J =8.6 Hz, 2H), 7.24 (d, J =8.4 Hz, 2H), 7.15 (d, J =8.4 Hz, 2H), 3.22 (t, J =7.5 Hz, 2H), 3.01 (t, J =7.5 Hz, 2H). 13 C NMR (101 MHz, CDCl 3 ) δ 197.90, 139.55, 135.50, 129.89, 129.61, 128.73, 128.46, 40.20, 29.33.…”
Section: Methodsmentioning
confidence: 99%
“…1‐(4‐bromophenyl)‐3‐(4‐chlorophenyl)propan‐1‐one (3 be) Yield 294.5 mg 91 % (Catalyst Ru1 ), 300.9 mg 93 % (Catalyst Ru2 ); 1 H NMR (400 MHz, CDCl 3 ) δ 7.78 (d, J =8.6 Hz, 2H), 7.57 (d, J =8.6 Hz, 2H), 7.24 (d, J =8.4 Hz, 2H), 7.15 (d, J =8.4 Hz, 2H), 3.22 (t, J =7.5 Hz, 2H), 3.01 (t, J =7.5 Hz, 2H). 13 C NMR (101 MHz, CDCl 3 ) δ 197.90, 139.55, 135.50, 129.89, 129.61, 128.73, 128.46, 40.20, 29.33.…”
Section: Methodsmentioning
confidence: 99%
“…[Cu(binap)I] 2 ( 1a ) was synthesized from BINAP and CuI in acetonitrile according to methods in the known literature . Then, [Cu(binap)I] 2 @HT ( 2 ) was prepared through our own method . With this heterogeneous Cu catalyst in hand, [Cu(binap)I] 2 @HT was used to catalyze the C—H hydroxylation of benzenethiol ( 3a ) and phenylboronic acid ( 4a ), and it was found that the desired product ( 5a ) could be obtained smoothly with moderate yield.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the heterogeneous [Cu(binap)I] 2 @HT ( 2a ) were prepared according to our recent method . Hydrotalcite (HT, 1.0 g) was dispersed in dimethyl sulfoxide (DMSO) (20 mL) by ultrasonic method (60 °C, 15 min, three times), and then was introduced to a 100imL Schlenk tube.…”
Section: Methodsmentioning
confidence: 99%
“…The use of magnetic Fe 3 O 4 as catalyst also did not result into the formation of the desired product 3aa (Table , entry 2). A literature survey suggests that nickel based catalyst has been employed for the activation of molecular hydrogen to generate nickel hydride and copper as a potential catalyst for borrowing‐hydrogen reactions . Keeping this thing in mind, NiFe 2 O 4 and CuFe 2 O 4 were employed as a catalyst for this reaction.…”
Section: Resultsmentioning
confidence: 99%